Direct Iterative Procedures for Consensus Building with Additive Preference Relations Based on the Discrete Assessment Scale - Wu, Zhibin (Springer Nature, 2020)
Individual consistency and group consensus are both important when seeking reliable and satisfying solutions for group decision making (GDM) problems using additive preference relations (APRs). In this paper, two new algorithms are proposed to facilitate the consensus reaching process, the ﬁrst of which is used to improve the individual consistency level, and the second of which is designed to assist the group to achieve a predeﬁned consensus level. Unlike previous GDMstudies for consistency and consensus building, the proposed algorithms are essentially heuristic, modify only some of the elements in APRs to reduce the number of preference modiﬁcations in the consistency and consensus process, and have modiﬁed preferences that belong to the original evaluation scale to make the generated suggestions easier to understand. In particular, the consensus algorithm ensures that the individual consistency level is still acceptable when the predeﬁned consensus level is achieved. Finally, classical examples and simulations are given to demonstrate the effectiveness of the proposed approaches.